The Pollution and Destruction of the Niger Delta Ecosystem in Nigeria:Who is to be blamed? - Bodo, Tombari; Gimah, Batombari Gbidum (European Scientific Journal, ESJ, 2020)
Petroleum exploration has brought a lot of revenue to the Nigerian government as most of the country’s investments and expenditures depend on the profits fromoil. However, the processes of petroleum exploitation over the years have resulted in the destruction of the Niger Delta ecosystem. Thus, this study aims to analyse the impact of pollution on the Niger Delta Ecosystem in Nigeria and identify persons responsible for the devastation. Consequently, published literatures, newspapers, stored recordings and other valuable materials on the Niger Delta region were reviewed extensively. The study revealed that the stakeholders (government, operating oil companies, and host community representatives) in the business of petroleum exploration have always denied their involvement in the pollution and destruction of the region, but the fact remains that the operating oil companies are responsible for the numerous spills from their rusty or outdated pipelines and the gases that are been flared in the region; the illegal refining and pipeline vandalism that are perpetrated by some members (militant groups) of the host communities have resulted in a more polluted environment; and government negligence in monitoring and supervising the oil operations in the region and ensure that polluted sites are adequately remediated had compounded the crisis and devastation in the region. All the stakeholders, in the business of petroleum exploration should accept responsibility of protecting the environment against further pollution by avoiding acts and practices that destroys the environment. In conclusion, the blame directly goes to the government, operating oil companies and the community representatives (militant groups, political leaders, traditional ruler, and village chiefs), as culprits for the destruction of the Niger Delta ecosystem.